Competências socioemocionais na formação e na prática docente: percepções de professoras da educação infantil - Rabelo, Jeriane da Silva (2021)
The scientific literature on the contributions of socio-emotional competences in the educational field has shown promising results through effective proposals to improve the school environment and favor the balance between the rational and emotional cognitive dimension of children. In this sense, it is important to identify what knowledge and practices can be traced so that socioemotional education becomes the guide for experiences in Early Childhood Education - EI. The research sought to understand the relevance of teaching socio-emotional competences in teacher training, pedagogical practice and in the relationship with the child, from the perspective of EI teachers. The studies that supported this work were made in the light of: Vygotsky (1991); Wallon (1995; 2007); Salovey and Sluyter (1999); Saltini (1997); Lefebvre (2001; Gardner (2005); Mora (2004); Sawaia (2006); Santos (2008); Campos (2010); Damásio (2011); Howard-Jone (2015). The investigation was carried out by means of: i) bibliometric analysis on the theme researched in the last ten years and ii) qualitative research, in the form of a case study with a sample composed of eighteen teachers from EI. The instrument used was the semi-structured interview. Data analysis occurred through the statistical description and content analysis of the respondents' answers with the support of the Iramuteq software. From the study (i), it was noticed that, in Brazil, emotional factors are ignored in most of the scientific studies analyzed, neglecting the life history of the subjects, in particular, of the EI teachers. In study (ii), it was found that the identification and regulation of emotions are crucial steps for the development of socio-emotional competence, in addition, the quality of the teachers' emotions was interconnected, mainly, with the school's environmental factors. Thus, it is expected to contribute, mainly, to the deepening of the understanding of the emotional elements involved in learning, training and educational practices in Early Childhood Education and, consequently, in the quality of the child's integral learning. In this respect, teaching knowledge and practices play an important role in the relationship between neuroscience - education - emotion and teacher training.